Breech presentation is a risk factor for dysplasia of the femoral trochlea - Øye, Christian R; Foss, Olav A; Holen, Ketil J (Acta orthopaedica, 2016)
Background and purpose - Instability of the patellofemoral joint is a common disorder in children and young adults. Although it has multifactorial causes, a shallow femoral trochlea is the single most important factor for instability. There is no consensus as to the etiology of trochlear dysplasia. We assessed whether the presentation of the fetus at birth could be a predisposing factor for trochlear dysplasia. Subjects and methods - We examined 348 knees in 174 newborns using ultrasonography, concentrating especially on the trochlea femoris. We measured the sulcus angle (SA) on a transverse scan. The way of fetal presentation at birth and standard parameters such as sex, gestational age, and length and weight at birth were registered. As breech presentation is a known risk factor for dysplasia of the hip, we also looked for an association between dysplasia of the femoral trochlea and dysplasia of the hips. Results - The mean SA was 148°. 17 knees in 14 children had an SA of >159°, which was defined as the threshold value for dysplasia. The incidence of breech position in these children was 15-fold higher. Of the different groups of breech positions, a child in frank breech with the knees locked in extension had a 45-fold increased risk of having trochlear dysplasia. Interpretation - For some newborns, a high sulcus angle can be found at birth, indicating that trochlear dysplasia can be found from birth. Breech presentation with knees extended appears to be a major risk factor for development of trochlear dysplasia.